Influence of planting material, plant population and organic manures on galangal (Kaempferia galanga L.) grown as intercrop in coconut (Cocos nucifera L.) garden - HEGDE, H P MAHESWARAPPA, H V NANJAPPA, M R (Journal of Spices and Aromatic Crops, 1999)
Field experiments conducted at Kasaragod, India to study the influence of planting material, plant population and organic manures on galangal (Kaempferia golanga) grown as intcrcrop in coconut (Cocos nucifcra) garden revealed that when mother rhizome was used as planting material significantly higher rhizome yield was achieved compared to finger rhizome. Plant population did not influence yleld. Farnl yard manure and major nutrient combinations recorded significantly higher yield compared to farm yard manure, vermicompost, composted coir pith and major nutrients applied alone.